COBIT 5 implementation - Information Systems Audit and Control Association (ISACA).; Information Systems Audit and Control Association (ISACA). (Rolling Meadows, IL. : ISACA, 2012)
Complements COBIT 5. Acts as a guide to provide a good practice approach for implementing GEIT based on a continual improvement life cycle that should be tailored to suit the enterprise's specific needs.
Includes bibliographical references.
oif 04/06/14
Loan
Keywords: COBIT (Information technology management standard); Information technology -- Security measures; Information technology -- Management; Business enterprises -- Information technology -- Security measures